Old Man’s Speech and Music. Sir 32:3 Interpreted by Clement of Alexandria and John Chrysostom - Szymański, Mikołaj (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2016)
The article tries to answer the question why Clement of Alexandria (Paed. II 58, 1–2) and John Chrysostom (De Eleazaro et septem pueris, PG, vol. 63, coll. 523–4) propose peculiar interpretations of Sir 32:3. At first sight it might seem that the writers used texts of that verse in the Septuagint that were different from its present shape, but the real causes of the discrepancies were, in Clement’s case, his abhorrence of music, and in John Chrysostom’s case, the situation in which his speech was delivered.